Liquid crystalline paracyclophane derivatives - Joachimi, Detlev; Ashton, Peter R.; Sauer, Christiane; Spencer, Neil; Tschierske, Carsten; Zab, Kerstin (Liquid crystals, 1996)
Various paracyclophane derivatives incorporating 4,4′-biphenyl, 2,5-diphenyl-1,3,4-thiadiazole, phenyl benzoate and 2,6-disubstituted naphthyl rigid cores were synthesized and their mesomorphic behaviour was studied using polarizing microscopy, DSC and X-ray diffraction. Most of these macrocyclic compounds possess liquid crystalline properties with unexpectedly high clearing temperatures compared to those of conventional calamitic mesogens. In this way, the coupling of two appropriate rigid units using flexible chains to form a macrocycle constitutes a new and powerful approach towards mesophase induction and stabilization. The types of mesophase formed by these macrocycles do not depend only on the nature of the bridging chains, but also strongly on the structure of the rigid aromatic system. The smectic A phase and the E phase are formed by polyetherbiphenylophanes. Poly-ethercyclophanes incorporating the 2,5-diphenylthiadiazole rigid core form nematic and smectic C phases. The nematic phase is the only mesophase when the rigid core is the phenyl benzoate unit. No mesomorphic properties could be detected for macrocycles which featured either the benzyl phenyl ether moiety or the 2,6-disubstituted naphthalene unit in their constitution.